Effect of living high and training low on sea level performance in runners - Nummela, A.; Jouste, P.; Rusko, H. (Medicine & Science in Sports & Exercise, 1996)
Runners (M = 4; F = 2) trained for 400 m lived for 10 days in a normobaric hypoxia in an altitude house (equivalent to 2,200 m) and trained outdoors at sea-level. Six male runners trained and lived solely at sea-level to serve as a control group. Measures were taken prior to and 3-5 days after acclimatization. A maximal anaerobic tests on a treadmill determined velocity at exhaustion and at 5 mM blood lactate level. The "altitude living" group improved 400 m race time, velocity at exhaustion (2.2%), and velocity at 5 mM lactate level. The sea-level trained group did not change in any measures. Implication: Although this study could be used to support the viability of living high and training low for enhancing training effects, the nature of the control group used has to be questioned. Only matched groups on important variables such as sex, performance, physiological capacities, and state of training would serve to offer definitive results on this topic. Since this was not provided, the conclusions of this investigation must be interpreted cautiously.